Trophodynamics as a Tool for Understanding Coral Reef Ecosystems - Bierwagen, Stacy L.; Heupel, Michelle R.; Chin, Andrew; Simpfendorfer, Colin A. (Frontiers in Marine Science, 2018)
The increased frequency of publications concerning trophic ecology of coral reefs suggests a degree of interest in the role species and functional groups play in energy flow within these systems. Coral reef ecosystems are particularly complex, however, and assignment of trophic positions requires precise knowledge of mechanisms driving food webs and population dynamics. Competent analytical tools and empirical analysis are integral to defining ecosystem processes and avoiding misinterpretation of results. Here we examine the contribution of trophodynamics to informing ecological roles and understanding of coral reef ecology. Applied trophic studies of coral reefs were used to identify recent trends in methodology and analysis. Although research is increasing, clear definitions and scaling of studies is lacking. Trophodynamic studies will require more precise spatial and temporal data collection and analysis using multiple methods to fully explore the complex interactions within coral reef ecosystems.